Formulation Development of Milk Pudding Substituted with Corn Milk - เรืองธรรมสิงห์ ฤทัย; ปิยะสุวรรณยิ่ง พรทิพย์; ศิริวงศ์ น้องนุช (KKU Science Journal, 2016)
The objective of this study was to develop pudding formula by substitution of corn milk for cow milk. The selected standard formula consisted of 36.5% milk, 14% sugar, 1.3% gelatin, 36.5% whipping cream, 11.6% egg york and 0.1% vanilla extract. The cow milk was substituted with corn milk at the level of 0 (control), 75 and 100%. The pudding formula with 100% corn milk substitution for cow milk and whipping cream (WC) was studied for comparison. The result showed that the most acceptable pudding was prepared from the formula with 100% corn milk replacement. Physical properties of the obtained pudding including L*, a*, b*, rupture strength and gel brittleness were 85.78, 4.30, 30.43, 105.47 g force and 9.94 mm, respectively. Nutritional values of the pudding with 100% corn milk could be comparable to those of the control whereas the percentage of calorie, carbohydrate and fat of the WC pudding decreased to 60.17, 36.49 and 73.80, respectively.